Exploring the Digital Literacy Levels of Junior High School Indonesian Language Teachers: A DigCompEdu Perspective - Gusti Putu Arya Arimbawa; I Made Indra Adhi Wikanta; I Wayan Sumarno; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (Jurnal Edutech Undiksha, 2024)
The advancement of digital technology requires educators to possess adequate digital literacy to effectively integrate technology into the teaching and learning process. However, digital literacy among subject teachers varies widely and requires special attention, especially in maximizing the use of technology to support educational practices. This study aims to provide an overview of the digital literacy levels of Indonesian language teachers at the junior high school level. The research employed a qualitative method with an online survey involving 72 Indonesian language teachers, selected through a cluster-quota sampling technique. The research instrument was a questionnaire adapted from the DigCompEdu model, comprising 22 core statements and 13 additional questions to explore the sample’s characteristics and teaching environment. Data were analyzed by comparing the percentage scores in each aspect of digital literacy within the DigCompEdu model. The results showed that most teachers reached the B1: Integrator level of digital literacy, reflecting their ability to integrate technology effectively into teaching. Teachers predominantly used digital technologies such as presentation media when teaching Indonesian language subjects. However, the study also identified several areas for improvement, including reflective practice, resource selection, teaching, evidence analysis, differentiation and personalization, and communication skills. This study concludes by emphasizing the importance of continuous digital literacy development to enable teachers to maximize the potential of technology in education.